The Temporal and Bidirectional Relationship Between Low Back Pain and Mental Health Disorders: A Systematic Review and Synthesis of Longitudinal Evidence - Tri Sandy Wibawa Mukti; Allan Yudhiatmoko; Eka Puji Lestari (International Medical Journal Corp. Ltd, 2025)
Introduction: Low back pain (LBP) is the leading global cause of disability. Its comorbidity with mental health disorders (MHDs) such as depression and anxiety is highly prevalent, complicating treatment and worsening prognosis. However, the temporal direction of this relationship remains ambiguous in cross-sectional literature. This systematic review synthesizes longitudinal evidence to clarify the bidirectional relationship between LBP and MHDs. Methods: A systematic review was conducted following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library databases were searched for prospective cohort studies published between January 1990 and December 2024. Inclusion was restricted to longitudinal studies assessing the bidirectional link: (1) baseline MHDs predicting new-onset LBP, or (2) baseline LBP predicting new-onset MHDs. Risk of bias was assessed using the Newcastle-Ottawa Scale (NOS). Results: Fifteen longitudinal studies met the inclusion criteria. The evidence confirms a significant bidirectional relationship. (1) Meta-analysis data from included reviews demonstrate that baseline depressive symptoms significantly increase the risk of developing new-onset LBP (pooled OR = 1.59; 95% CI 1.26–2.01) (Pinheiro et al., 2015). (2) Conversely, baseline chronic LBP (CLBP) prospectively predicts the onset of depression (OR = 1.28; 95% CI 1.01-1.61) (Dickson et al., 2022) and dysthymia (HR = 1.53) (Schmaling and Nounou, 2018). Comorbid MHDs are significant prognostic indicators for worse LBP outcomes, including higher pain intensity (P=0.11), greater disability (P=0.16), and poorer recovery (RR=0.91) (Pinheiro et al., 2016). Discussion: The synthesis of longitudinal evidence confirms a reciprocal, prognostically significant relationship. This comorbidity is not incidental but is underpinned by shared neurobiological pathways, including monoaminergic system disruption (serotonin, norepinephrine), Hypothalamic-Pituitary-Adrenal (HPA) axis dysregulation, and neuroplastic changes in shared brain regions (e.g., anterior cingulate cortex, prefrontal cortex). The findings mandate a shift from a purely biomedical to an integrated biopsychosocial (BPS) model of care. Conclusion: The relationship between LBP and MHDs is bidirectional and significant. We recommend the implementation of routine, integrated screening protocols and multidisciplinary treatment pathways to address this comorbidity, as treating either condition in isolation is likely to be ineffective.